2018
DOI: 10.1002/2017wr020748
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Suspended Clay to Open and Sand‐Filled Framework Gravel Beds in a Laboratory Flume

Abstract: Pulses of fine sediment composed of sand, silt, and clay can be introduced to gravel bed rivers through runoff from burn‐impacted hillslopes, landslides, bank failure, or the introduction of reservoir sediment as a result of sluicing or dam decommissioning. Here we present a study aimed at quantifying exchange between suspensions of clay and gravel beds. The questions that motivate the work are: how do bed roughness and pore space characteristics, shear velocity ( u∗), and initial concentration (C0) affect cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
9
29
0
1
Order By: Relevance
“…This amount of bed erosion is realistic as suggested by the observed cross sectional changes (see Figure S4.1) and vertical scouring estimation in Misset et al (). This simple analysis supports the existence of efficient sediment exchanges between the flow and the bed subsurface as proposed by several authors (Mooneyham & Strom, ; Mueller & Pitlick, ; Park & Hunt, ) and discussed in the next section.…”
Section: Discussionsupporting
confidence: 89%
“…This amount of bed erosion is realistic as suggested by the observed cross sectional changes (see Figure S4.1) and vertical scouring estimation in Misset et al (). This simple analysis supports the existence of efficient sediment exchanges between the flow and the bed subsurface as proposed by several authors (Mooneyham & Strom, ; Mueller & Pitlick, ; Park & Hunt, ) and discussed in the next section.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is consistent with observations made in several flume and field studies considering sand, silt or clay particle infiltration in porous beds [Frostick et al, 1984;Glasbergen, 2014;Hamm et al, 2009;Harvey et al, 2012;Krishnappan and Engel, 2006;Mooneyham and Strom, 2018]. This infiltration process was found to occur even for very low Rouse numbers (~0.01), especially when pore spaces were empty [Khullar, 2007;Mooneyham and Strom, 2018].…”
Section: River Bed Mobilitysupporting
confidence: 90%
“…Similar observations were made at the reach scale in the Isabena catchment where changes in fine sediment stocks were correlated with the maximum flood discharge [Buendia et al, 2016]. The strong interactions observed in these field studies between suspended load and the river bed were also demonstrated in several flume experiments [Glasbergen, 2014;Hamm et al, 2009;Krishnappan and Engel, 2006;Mooneyham and Strom, 2018]. Navratil et al (2010) estimated these stocks in a typical mountainous braided river by considering stocks in dried braided channels, bars and vegetated bars in addition to sediments stored in the wetted channel.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Experiments and a physico‐chemical model demonstrated that advection (driven by hyporheic flow associated with interactions between stream flow and bedform), particle settling, and retention (filtration) are the major process that influence the colloid exchange between the stream and streambed (Jin et al, ; Packman et al, , ). Particle settling enhanced colloid deposition in the hyporheic zone (Fries & Trowbridge, ), which in turn changed the bed properties including porosity and hydraulic conductivity (Mooneyham & Strom, ). There were also simulations with considering particle aggregation effects on colloid exchange between the stream and streambed based on a pumping exchange model (Areepitak & Ren, ).…”
Section: Introductionmentioning
confidence: 99%